Factors Influencing Quiet Quitting: An Exploration of Work Stress as a Moderating Variable - Anak Agung Gede Marta Pratama; Nyoman Sri Subawa (Dinasti International Journal of Education Management and Social Science, 2025)
The phenomenon of quiet quitting has gained attention as it reflects employees’ tendency to perform only basic tasks without additional involvement. This study aims to analyze the influence of job burnout, workplace bullying, and work conflict on quiet quitting, while exploring the role of work stress as a moderating variable. A quantitative approach was employed, with data collected through questionnaires distributed to respondents from various sectors. The findings reveal that job burnout, workplace bullying, and work conflict have a positive and significant effect on quiet quitting. Furthermore, work stress was found to moderate the relationship between these factors and quiet quitting, where higher levels of stress amplify the negative impact of burnout, bullying, and conflict on employees’ tendency to engage in quiet quitting. These results emphasize the importance of stress management and workplace climate improvement to reduce the potential occurrence of quiet quitting within organizations.